(untitled) (Journal of Hama University, 2024)
The aim of the research is to know the level of role conflict among teachers working in the educational sector in the city of Aleppo. And to reveal the differences in the conflict according to some variables (number of years of school service at work, place of residence and the occupational status of husband).The researcher built a scale of role conflict and applied it to a sample consisting of (91) female teacher, who followed the descriptive approach in the research and reached the following results: there are no statistically significant differences between the average scores of the sample members and the hypothetical average of the scale, as meaning that the level of conflict among the sample members is within the average. From the dimension (housework, self-relationship disorder, negligence towards the husband), while no statistically significant appeared in the role conflict of female teachers on the dimension of caring for and no significant differences approach in the role conflict according to the variables (number of years of school service at work, place of residence and the occupational status of husband).